The Effect of Workload on Work Stress and Work Life Balance (Study on Employees at PT. Hatten Bali Tbk Distribution Division) - Pramesti, Ni Putu Nirmala Suzanne; Adnyani, I Gusti Ayu Dewi (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study aims to analyze the effect of workload on work stress and work life balance among employees of PT. Hatten Bali Tbk Distribution Division, as well as to examine the mediating role of work life balance in this relationship. This study uses a quantitative approach with a causal associative design. All employees of the distribution division, totaling 36 people, were used as respondents through the census method. Data were collected through questionnaires and interviews, then analyzed using path analysis with IBM SPSS. The results show that workload has a positive and significant effect on work stress, and has a negative and significant effect on work life balance. Work life balance has a negative and significant effect on work stress and is proven to mediate the effect of workload on work stress. These findings indicate that proper workload management and the creation of balance between work life and personal life are crucial to reduce employee work stress and improve their well-being.